The Relationship Between Father Involvement in Parenting and Resilience of Children Aged 5-6 Years in Sukamanah Village, Bekasi Regency - Ariana Kusuma; Ine Nirmala; Nur Rochimah (PUSAKA: Journal of Educational Review, 2026)
Fathers' involvement in parenting plays a crucial role in supporting children's social, emotional, and psychological development. However, the increasing prevalence of fatherlessness and limited paternal involvement in Indonesia has raised concerns regarding children's resilience. This study aimed to examine the relationship between fathers' involvement in parenting and the resilience of children aged 5–6 years in Sukamanah Village, Bekasi Regency. This study employed a quantitative approach using a correlational research design. The study population consisted of 127 children aged 5–6 years enrolled in 11 kindergarten and early childhood education (ECE) institutions in Sukamanah Village. Using the Slovin formula with a 10% margin of error, 65 respondents were selected as the study sample. Data were collected through closed-ended questionnaires administered to parents, particularly fathers, and analyzed using descriptive and correlational statistical techniques. Fathers' active involvement in parenting contributes significantly to the development of resilience in children aged 5–6 years. Strengthening fathers' participation in child-rearing is expected to enhance children's ability to adapt, regulate emotions, overcome challenges, and support their overall development and well-being.